Diseño de una red híbrida (fibra-coaxial) para ofrecer servicios de banda ancha para la empresa Cinecable tv en la Ciudad De Quevedo - Cedeño Macías, Eliana Beatriz (2016)
Currently networks fulfill functions for the transport of all types of information as well as the data that are sent or received by the different means wired and wireless existing through the application of technologies and techniques that have improved the communication processes; in this way with the development of the present project take advantage of the earnings that generate the same, designing a model of hybrid network (Fibre- Coaxial) for the Cinecable TV of Quevedo company using the coaxial deployed network infrastructure allowing you to offer triple play (fixed telephony, television and internet) services, not only benefiting the subscribers but it also, the company will reduce costs for implementation, equipments and maintenance that they required for a new network that allows them obtain these same products to clients. In addition this proposal it is based on the opportunity to add or modify telecommunication services that the company has access in its concession contract obtained through by the ARCOTEL before SUPERTEL . Basically this research to announce the elements that to make up the infrastructure of network, equipments and offered coverage and subscribers that currently has Cinecable TV, also displayed the model of hybrid network designed, characteristics and requirements of equipments for its operation, reference information both for resolutions as for the laws that endorse the enlargement or request of the required services for this types of companies.